2019
DOI: 10.3390/nano9040591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poly(Amidoamine) Dendrimer-Coated Mesoporous Bioactive Glass Nanoparticles on Dentin Remineralization

Abstract: Dentin hypersensitivity (DH) is one of the most common clinical conditions usually associated with exposed dentinal surfaces. In this study, we identified the effectiveness of poly(amidoamine) (PAMAM) dendrimer-coated mesoporous bioactive glass nanoparticles (MBN) (PAMAM@MBN) on DH treatment, examining the ion-releasing effect, dentin remineralization, and the occluding effect of dentinal tubules. We synthesized MBN and PAMAM@MBN. After soaking each sample in simulated body fluid (SBF), we observed ion-releasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Characterization of the GaMBN-containing resins confirmed that the Ga 3+ , Ca 2+ , and PO 4 3− ions formed the same heterogeneous structure as the previous study [18]. Moreover, the N 2 adsorption-desorption isotherm results determined that the resins have uniform pore structures (type IV isotherms) as shown in the previous study [17]. Ion release tests demonstrated that ions were barely released by GaMBN0, and that ion release increased with the GaMBN concentration.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Characterization of the GaMBN-containing resins confirmed that the Ga 3+ , Ca 2+ , and PO 4 3− ions formed the same heterogeneous structure as the previous study [18]. Moreover, the N 2 adsorption-desorption isotherm results determined that the resins have uniform pore structures (type IV isotherms) as shown in the previous study [17]. Ion release tests demonstrated that ions were barely released by GaMBN0, and that ion release increased with the GaMBN concentration.…”
Section: Discussionsupporting
confidence: 83%
“…The GaMBN was synthesized using the modified sol-gel process reported in a previous study [17]. First, 10 mL of 2-ethoxyethanol (Sigma-Aldrich, St. Louis, MO, USA), 2 mL of aqueous ammonia (Samchun, Pyeongtaek, South Korea), and 0.788 g of calcium nitrate tetrahydrate (Ca(NO 3 ) 2 •4H 2 O; Sigma-Aldrich, St. Louis, MO, USA) were added to 150 mL of distilled water along with 20 mL of ethanol and 1 g of hexadecyltrimethylammonium bromide (CTAB; Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Synthesis Of Ga-doped Mesoporous Bioactive Glass Nanoparticlmentioning
confidence: 99%
“…The absorption peaks at 1220-1250 cm −1 were attributed to C-OH, C-C stretching, and -OH bending vibrations [13]. As shown in Figure 4(b), the stretching frequency (1643 cm −1 ) corresponding to O-H also shifted to 1639 cm −1 due to the chemical bonds of GOQD and MBN in MBN@GOQD sample [13,24]. .…”
Section: Graphene Oxide Quantum Dots Coated Mesoporous Bioactive Glasmentioning
confidence: 89%
“…The weak peak at 562 cm −1 appears to be the P-O band of phosphate group. The peak of 874, 1424, and 1469 cm −1 appears to be the C-O band of calcium carbonate [13].…”
Section: Graphene Oxide Quantum Dots Coated Mesoporous Bioactive Glasmentioning
confidence: 97%
See 1 more Smart Citation